A CLINICAL EVALUATION REPORT OF PERFORMANCE OF BPL DIGITAL BLOOD PRESSURE MONITOR, B20, MEASURED BY OSCILLOMETRIC METHOD AS COMPARED TO THE VALUE MEASURED BY AUSCULTATION WITH A MERCURY SPHYGMOMANOMETER - Dr. Chidananda; Dr. Kamran; Siddhant (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This clinical evaluation report presents the performance validation of the BPL Medical 120/80 B20 digital blood pressure monitor, which employs the oscillometric method. The study was conducted in accordance with the ANSI/AAMI/ISO 81060-2:2013 guidelines to compare its accuracy against traditional auscultation using a mercury sphygmomanometer. Conducted at Ananya Multispecialty Hospital, Bangalore, the study involved 162 subjects, ensuring diverse representation by gender and age as per the guidelines. The results demonstrated that the BPL 120/80 B20 meets the stringent accuracy criteria set by ANSI/AAMI/ISO, with mean differences between observer and device readings well within the acceptable range of ±5.2 mmHg for systolic and ±5.65 mmHg for diastolic measurements. These findings confirm that the BPL 120/80 B20 is a reliable and accurate device for blood pressure monitoring, supporting its compliance with international standards for non-invasive sphygmomanometers.